Revision of the European species of the genus Hincksina Norman, 1903 (Bryozoa, Cheilostomatida, Flustridae) - Berning, Björn; Jones, Mary E. Spencer; Vieira, Leandro M. (Zootaxa, 2021)
Four Atlantic species of the flustrid genus Hincksina Norman, 1903, which were introduced during the 19th and early 20th century, are redescribed and imaged: Hincksina flustroides (Hincks, 1877) from Great Britain, Hincksina sceletos (Busk, 1858) from Madeira as well as Hincksina neptuni (Jullien in Jullien & Calvet, 1903) n. comb. and Hincksina alice (Jullien in Jullien & Calvet, 1903) n. comb. from the Azores, the latter two of which were hitherto placed in the cribrilinid genus Membraniporella Smitt, 1873. Lectotypes are designated for all species. A new species, Hincksina synchysia n. sp., is introduced for the Mediterranean taxon previously referred to as Hincksina flustroides f. crassispinata Gautier, 1962. In contrast to species from the continental shelf, which have simple cylindrical or flattened spines, some of the species from the oceanic islands of Madeira and the Azores are particularly characterised by falciform and variably formed palmicorn spines. Moreover, whilst most Hincksina species have avicularia with a relatively short, (sub)rounded rostrum and mandible, the two Azorean species have elongated, curved and pointed avicularia. The relationship between Gregarinidra Barroso, 1949, which also has pointed avicularia, and Hincksina is commented upon. Based on several shared diagnostic characters, the genus Cribralaria Silén, 1941 is here transferred from the Cribrilinidae Hincks, 1879 to the Flustridae Fleming, 1828.